PENGARUH MENGUNYAH BUAH APEL DAN JAMBU BIJI MERAH TERHADAP DEBRIS INDEKS - Siti Hidayati; Dwi Suyatmi (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2016)
TITLEThe effect of apple and guava chewing to debris indexABSTRACTDebris is food accumulation contained in the oral cavity, if not promptly cleaned will cause dental caries disease. Debris can be cleaned mechanically or chemically. One of the way to clean debris by chewing apples and guava, fibrous texture and juicy fruit, so it can clean teeth naturally. The purpose of this study was to determine the effect of chewing an apple and red guava against debris index.This research method is quasy experimental with pre and post test design. Population were students aged 8-10 years. Samples are 40 students who were divided into 2 groups: 20 students as treatment group chewing apples and 20 students chewing guava as control group. Sampling using total sampling techniques. Independent variables was munching apples and guava red while dependent variable was debris index,Results: from paired T test showed the results of p = 0.000, mean p 0.05, while the independent T test showed the results of p = 0,001, meaning p Value of 0.05. Conclusion: Chewing apples and guava red effect on the index debris. Chewing apples are more effective than chewing guava in decreasing debris index. Key words : apple, guava red, debris index